A minimal fate-selection switch. (December 2015) - Weinberger, Leor S
Abstract : To preserve fitness in unpredictable, fluctuating environments, a range of biological systems probabilistically generate variant phenotypes — a process often referred to as 'bet-hedging', after the financial practice of diversifying assets to minimize risk in volatile markets. The molecular mechanisms enabling bet-hedging have remained elusive. Here, we review how HIV makes a bet-hedging decision between active replication and proviral latency, a long-lived dormant state that is the chief barrier to an HIV cure. The discovery of a virus-encoded bet-hedging circuit in HIV revealed an ancient evolutionary role for latency and identified core regulatory principles, such as feedback and stochastic 'noise', that enable cell-fate decisions. These core principles were later extended to fate selection in stem cells and cancer, exposed new therapeutic targets for HIV, and led to a potentially broad strategy of using 'noise modulation' to redirect cell fate.